The role of the construction sector in Ghana - Nkechi S. Owoo; Monica P. Lambon-Quayefio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The research explores the structure and performance of Ghana's construction subsector, in light of the country's 2007 oil discovery. Using primary and secondary data resources, we discuss how marginal costs and expenditure shocks may vary within the construction sector for subsectors such as housing, roads, and other important social infrastructure such as drainage. We analyse expenditure shocks that may result from inflation and price dynamics, finding that construction sector costs are closely related to exchange rate movements. We identify key bottlenecks to the supply response of the sector and recommend institutional and policy reforms to improve performance and output.
Keywords: E31; F31; O25; Y10; 330; construction sector; price dynamics; expenditure shocks; marginal costs; Ghana